Association of IL-18 polymorphisms with rheumatoid arthritis and systemic lupus erythematosus in Asian populations: a meta-analysis - Chen Shuilian; Jiang Feng; Ren Jiangping; Liu Jiajing; Meng Wei (BMC, 2012)
Abstract Background Interleukin (IL)-18, an important proinflammatory cytokine, plays a potential pathological role in rheumatoid arthritis (RA) and systemic lupus erythematosus (SLE). Studies on the relationship of IL-18 gene promoter rs1946518 (−607A/C) polymorphism, rs187238 (−137G/C) polymorphism with RA and SLE are inconclusive. The aim of this study was to get a more precise estimation of the relationship in Asian populations. Methods Meta-analysis was conducted on the associations between the IL-18 (−607A/C and -137G/C) polymorphisms and RA and SLE, using; (1) allele contrast, (2) dominant, and (3) recessive models. A total of 11 studies were included in this study. Results For the relationship of IL-18 rs1946518 polymorphism with RA (additive model: OR=0.752, 95%CI=0.562-1.006; dominant model: OR=0.730, 95%CI =0.479-1.113; recessive model: OR=0.537, 95%CI=0.271-1.064) and SLE (additive model: OR=0.684, 95%CI=0.455-1.028; dominant model: OR=0.645, 95%CI=0.368-1.130; recessive model: OR=0.672, 95%CI =0.447-1.010), no significant association with RA and SLE risk can be found under all genetic models in Asian populations. However, significant associations were observed in Chinese population for both RA ((OR=0.688, 95%CI =0.532-0.889) and SLE (OR=0.606, 95%CI =0.396-0.930) under additive model. For the relationship between IL-18 rs187238 polymorphism and RA or SLE, there was no significant association detected in all genetic models, even in Chinese population. Conclusions This meta-analysis indicates that the IL-18-607A/C polymorphism may confer susceptibility to RA and SLE in Chinese population, but not all Asians.